HUBUNGAN KECERDASAN EMOSIONAL DAN PERILAKU SOSIAL DENGAN KETERAMPILAN KOLABORASI DALAM PEMBELAJARAN - Nur Afif; Ahmad Fauzi (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2022)
This study aims to examine and find out empirical data regarding the relationship between emotional intelligence and social behavior with student collaboration skills in learning, either partially or simultaneously. This study uses a survey method with data collection tools using a questionnaire that is preceded by direct observation and interviews with data sources, namely undergraduate students of the Faculty of Engineering, Islamic University 45 Bekasi as the population. While the sampling in this study used a cluster sampling technique by taking the fourth semester students at the Faculty of Engineering, Islamic University 45 Bekasi, amounting to 70 students. The data analysis used is correlation and regression analysis which is described descriptively. The results of this study indicate that there is a positive and significant relationship between emotional intelligence and student collaboration skills in learning with a correlation coefficient of 0.917 and a coefficient of determination of 84.1%. Second, there is a positive and significant relationship between social behavior and student collaboration skills in learning with a correlation coefficient of 0.704 and a determination coefficient of 49.6%. Third, there is a positive and significant relationship between emotional intelligence and social behavior together with student collaboration skills in learning with a correlation coefficient of 0.919 and a coefficient of determination of 84.5%.